Neonatal breast swelling - not always physiological - Inês Pedrosa; Catarina Cordeiro; João do Agro (Hygeia Press di Corridori Marinella, 2022)
Neonatal mastitis is a rare condition, usually with a good prognosis and no recurrence. Characteristic clinical findings are unilateral swelling, erythema, warmth, tenderness, and/or induration of the breast. Systemic symptoms are uncommon. The microbiological diagnosis is an important step in the clinical approach, with Staphylococcus aureus being the most identified causative organism. Treatment recommendations include antibiotic therapy followed by either surgical incision or needle aspiration if medical therapy fails. A previously healthy, 38-day-old girl presented with a 2-week history of breast asymmetry, initially discrete and then followed by a gradual increase in size and inflammatory signs of the left breast. On physical examination, she had unilateral swelling, erythema, warmth and induration of the left breast, fluctuation and nipple involution. No purulent discharge was observed. She underwent an ultrasound that revealed a breast abscess. She was started on oral antibiotics, with a posterior switch to the parenteral route, but no clinical improvement was found. Therefore, the patient was referred to surgical drainage, with a good clinical evolution afterward.  In conclusion, the diagnosis of neonatal breast abscess was made due to exuberant clinical inflammatory local signs and poor response to oral antibiotic therapy. It was successfully treated with combined surgical and medical management. This case shows that a good outcome may be achieved with timely diagnosis and adequate treatment.